2018
DOI: 10.1002/chem.201705784
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Free Synthesis of Hierarchical SSZ‐13 Microspheres with High MTO Catalytic Activity

Abstract: Hierarchical SSZ-13 microspheres, with abundant mesoporous channels, have been successfully synthesized by addition of calcined SSZ-13 crystals in the starting gel in the absence of any organic templates. This strategy not only remarkably reduces the production cost and environmental pollution, but also significantly decreases the crystallization time as well as evidently reducing the zeolite crystal sizes in many cases. The synthesized sample was characterized by XRD, BET, ICP, SEM, TEM, TG, and NH -TPD, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…These mesoporous SSZ-13 catalysts can be regenerated without losing activity [50]. Furthermore, the hierarchical SSZ-13 catalyst obtained using template-free synthesis exhibits excellent performances in methanol to light olefins, with methanol conversion as high as 100%, high light olefin selectivity at 90%, and with an improved catalyst lifetime compared to a conventional catalyst [54] as shown in Figure 3.…”
Section: Methanol and Ethanol To Light Olefinsmentioning
confidence: 98%
“…These mesoporous SSZ-13 catalysts can be regenerated without losing activity [50]. Furthermore, the hierarchical SSZ-13 catalyst obtained using template-free synthesis exhibits excellent performances in methanol to light olefins, with methanol conversion as high as 100%, high light olefin selectivity at 90%, and with an improved catalyst lifetime compared to a conventional catalyst [54] as shown in Figure 3.…”
Section: Methanol and Ethanol To Light Olefinsmentioning
confidence: 98%
“…Hierarchically porous zeolites can also be prepared without the employment of secondary hard or soft templates. Several methods including engineering of intergrowth, , additive-assisted crystallization, ,, seed-induced synthesis, , a controlled crystallization process, ,, and designing special structure-directing agents have been reported for the synthesis of hierarchically porous zeolites in the absence of organic templates.…”
Section: Synthesismentioning
confidence: 99%
“…In this synthesis strategy, seed crystals of the target zeolite are synthesized using the conventional method with an SDA, and then, a small amount of the as-synthesized zeolite seeds are added to the organic template-free reactant gel to form the desired zeolite phase. The added zeolite seed crystals increase the nucleation and crystallization rate and enhance the quality of the desired zeolite phase by improving the crystallization. Hierarchical SSZ-13 microspheres, with abundant mesoporous channels, have been successfully synthesized by adding calcined SSZ-13 zeolite crystals in the starting gel without organic templates . This strategy not only remarkably reduced the production cost and environmental pollution but also significantly decreased the crystallization time and reduced the zeolite crystal sizes.…”
Section: Synthesismentioning
confidence: 99%
“…The zeolite Beta obtained by using the seed assisted approach has been widely used for different applications such as; gas adsorption [26a] and catalysis. [26b] In addition to Beta zeolite, the other zeolite frameworks such as; ZSM-5, [27] SSZ-13, [28] CHA, [29] NaY, [30] SUZ-4, [31] LEV, [32] and MTW [33] zeolite have also been prepared using the seed-assisted strategy (Table 1, entries [16][17][18][19][20][21][22]. These zeolite frameworks have been explored for different organic transformations and gas separation.…”
Section: Seed-assisted Synthesismentioning
confidence: 99%
“…These zeolite frameworks have been explored for different organic transformations and gas separation. [27][28][29][30][31][32][33] The seed assisted method has also been reported for the synthesis of selective zeolite framework by using the seed of other zeolite frameworks. Xiao et al have reported the selective synthesis of ZSM-34 using a small proportion of zeolite L in the synthesis composition of ZSM-34 (( Table 1, entry 23).…”
Section: Seed-assisted Synthesismentioning
confidence: 99%